Distribution of ESBL-Producing Enterobacteriaceae with Carbapenem Resistance in Dr. H. Abdul Moeloek General Hospital, Lampung, Indonesia - Hidayat Hidayat; Muhammad Nur (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2026)
Enterobacteriaceae producing Extended-Spectrum Beta-Lactamase (ESBL) and resistant to carbapenem class antibiotics impact the high mortality rate and limitations in therapy.. This study aimed to assess the prevalence of ESBL-producing Enterobacteriaceae and Carbapenem resistant too in clinical isolates obtained from Dr. H. Abdul Moeloek General Hospital, Lampung. A total of 311 Enterobacteriaceae isolates were collected from various clinical specimens, including blood, urine, sputum and wound cultures, between January to December 2022. Identification and antimicrobial susceptibility testing were performed using standard microbiological techniques, with VITEK2 compact automated system. Carbapenem resistance and ESBL production were detected automatically. The results was found prevalence a 1,93% of Enterobacteriaceae ESBL-producing strains and carbapenem resistant, consisting of 50 % in Escherichia coli, 33,4 % in Klebsiella pneumoniae and 16,6% in Burkholderia cepacia. The study also found significant resistance patterns to other common antibiotics, highlighting the urgent need for improved surveillance and antimicrobial stewardship practices, continuous monitoring and the development of effective strategies to combat the growing threat of multidrug-resistant organisms in hospital.